Towards a personal robotics development platform: Rationale and design of an intrinsically safe personal robot - Wyrobek, K.A.; Berger, E.H.; Van der Loos, H.F.M.; Salisbury, J.K. (2008 IEEE International Conference on Robotics and Automation, 2008)
The most critical challenge for Personal Robotics is to manage the issue of human safety and yet provide the physical capability to perform useful work. This paper describes a novel concept for a mobile, 2-armed, 25-degree-of- freedom system with backdrivable joints, low mechanical impedance, and a 5 kg payload per arm. System identification, design safety calculations and performance evaluation studies of the first prototype are included, as well as plans for a future development.